Road Geometry Planning on Horizontal Curves Using AutoCADÂ® Civil 3D: A Case of Mujahiddin â€“ Lampok Road, Nusa Tenggara Barat - Bayu Endoriawan; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2023)
Indonesia is a country that has a large forest area, making it famous for its wood industry. The wood industry is processed into various kinds of furniture to be exported to all cities and countries. The connecting road between Mujahiddin-Lampok Road is made to support the economic activities of residents as Copper and gold suppliers. This research aims to design road geometrics, especially horizontal alignments by the